Work Behavior from the Qur’anic Perspective - Zainal Adnan, Ahmad Amri; Mastor, Khairul Anwar; Kasan, Hasnan; Mohamad Hamzah, Firdaus (International Business Education Journal, 2017)
The concept of work behavior and its constructs derived from numerous approaches and disciplines. However, in the making of these work behavior constructs, religion has often been sidelined. Islamic management scholars have come up with Islamic work behavior theories according to the Qur’an and hadiths, but there is hardly enough empirical proof to support these theories. This paper aimed to determine the constructs of work behavior from the Qur’anic perspective using the empirical method. The foundation of the constructs and items in the instrument are derived from the Qur’an and hadiths. A total of fifty-one items were extracted from verses of the Qur’an and hadiths. The content validity of the items was determined by consulting subject matter experts from the Faculty of Islamic Studies and Psychology, while factor analysis was used to analyze the reliability of the constructs. Data from respondents of a public university in Malaysia was analyzed using principal component factor analysis. Six sub-constructs were extracted from two main constructs which are al-Qawiy (Ability) and al-Amin (Trustworthiness). The two main constructs have an alpha coefficient of .95 and .94 respectively. The al-Qawiy construct consists of three sub-constructs, which are Professional, Competent and Sensitive with alpha coefficient values of .93, .90 and .85 respectively. As for the al-Amin construct, which also consists of three sub-constructs namely Integrity, Just and Principled, the alpha coefficient values are .88, .89 and .85 respectively. The outcome of this research proves that Islam integrates human nature and practical needs in a working surrounding across time. The output contributed to the literature of related research fields such as the psychology of religion, organizational psychology, and management, thus providing an alternative to assess Muslims’ work behaviors with more reliability.